2019
DOI: 10.23736/s0031-0808.18.03568-1
|View full text |Cite
|
Sign up to set email alerts
|

Competence in navigation and guided transbronchial biopsy for peripheral pulmonary lesions

Abstract: A B S T R A C TOptions for non-surgical tissue diagnosis of the peripheral nodule include CT scan-guided TTNA, fluoroscopy-guided bronchoscopy, radial endobronchial ultrasound (EBUS), electromagnetic navigation bronchoscopy (ENB), and virtual bronchoscopy navigation (VBN). For physicians who choose to pursue non-surgical biopsy, the decision to perform CT scan-guided or ultrasound-guided TTNA, conventional bronchoscopy or bronchoscopy guided by EBUS, ENB, or VBN will depend on a number of factors. CT scan-guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Rapid identification of the nature of pulmonary lesion with a likelihood of malignancy is a critical task in the early diagnosis of lung cancer and is worthy of all efforts. Many transbronchial guided methods have been developed to improve the diagnostic yield and especially increase the safety in the high‐risk group for percutaneous lung biopsy 14 . However, until now, CT‐guided percutaneous lung biopsy cannot fully replace one another because of its high diagnostic yield of 95.0%‐98.4%, sensitivity and specificity for the detection of malignancy 15‐17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid identification of the nature of pulmonary lesion with a likelihood of malignancy is a critical task in the early diagnosis of lung cancer and is worthy of all efforts. Many transbronchial guided methods have been developed to improve the diagnostic yield and especially increase the safety in the high‐risk group for percutaneous lung biopsy 14 . However, until now, CT‐guided percutaneous lung biopsy cannot fully replace one another because of its high diagnostic yield of 95.0%‐98.4%, sensitivity and specificity for the detection of malignancy 15‐17 .…”
Section: Discussionmentioning
confidence: 99%
“…Many transbronchial guided methods have been developed to improve the diagnostic yield and especially increase the safety in the high-risk group for percutaneous lung biopsy. 14 However, until now, CT-guided percutaneous lung biopsy cannot fully replace one another because of its high diagnostic yield of 95.0%-98.4%, sensitivity and specificity for the detection of malignancy. [15][16][17] Although CT-guided biopsy uses a smaller radiation dose than conventional diagnostic CT, the study by Pearce et al reported that even a relatively low irradiation from medical imaging in childhood can result in a small but excess risk for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is now broadly accepted that screening for lung cancer reduces cancer mortality [ 11 ]. For this reason, the pulmonologist can expect the referral of more patients with small lung lesions, and in line with this, training techniques and programs in endoscopic procedures for novice operators are gaining increasing interest [ 12 , 13 ]. However, especially concerning the more recent invasive endoscopic procedures on the market, such as ENB, there is still huge need for knowledge about what factors influence diagnostic yield when inexperienced operators perform ENB in order to select suitable patients and to decide when expert supervision is needed.…”
Section: Introductionmentioning
confidence: 99%